PERLINDUNGAN HUKUM TERHADAP PELAKU PENCURIAN YANG DIHAKIMI OLEH MASYARAKAT MEDAN YANG DAPAT BERAKIBAT KEMATIAN BAGI PELAKU - Banjarnahor, Bua Masro; Yudarwin, Yudarwin (Universitas Ekasakti, 2022)
Theft is an act where someone takes goods outside their rights without the permission of the owner of the goods, the number of theft cases in Medan has resulted in the action of the main judge himself by the people of Medan against the perpetrators of theft growing. vigilante action is less insurmountable. The level of crime that results in public judgment against the perpetrators of the crime of theft consists of two levels of crime, namely theft which is carried out repeatedly and the theft accompanied by the part or violence, in the second is a part that often occurs why the perpetrators of theft are often persecuted by the public. especially the Medan area of North Sumatra. The importance of legal protection for perpetrators of theft caught red-handed by the people of Medan is not to protect their actions but to protect the human rights that he (the thief) has regulated by the existing law in Indonesia, where the perpetrators have the right to be tried under positive Indonesian law in order to suppress their actions. This vigilante anarchist does not happen again, especially in the Medan area.